2016
DOI: 10.1042/bcj20160154
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain regulation of the ATPase activity of the ABC transporter haemolysin B from Escherichia coli

Abstract: Type 1 secretion systems (T1SS) transport a wide range of substrates across both membranes of Gram-negative bacteria and are composed of an outer membrane protein, a membrane fusion protein and an ABC (ATP-binding cassette) transporter. The ABC transporter HlyB (haemolysin B) is part of a T1SS catalysing the export of the toxin HlyA in E. coli HlyB consists of the canonical transmembrane and nucleotide-binding domains. Additionally, HlyB contains an N-terminal CLD (C39-peptidase-like domain) that interacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 60 publications
5
24
0
Order By: Relevance
“…Thus, ATP hydrolysis is clearly important for ABC transporter mediated substrate translocation, we determined the in vitro activity of NisT in terms of ATPase rate without and with substrate. Here, the basal ATPase activity had a value of 79.9 ± 2.9 nmol•min −1 •mg −1 with a K m value of 0.37 ± 0.04 mM, which is in the range of other ABC transporters [51][52][53][54] (Fig. 3).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, ATP hydrolysis is clearly important for ABC transporter mediated substrate translocation, we determined the in vitro activity of NisT in terms of ATPase rate without and with substrate. Here, the basal ATPase activity had a value of 79.9 ± 2.9 nmol•min −1 •mg −1 with a K m value of 0.37 ± 0.04 mM, which is in the range of other ABC transporters [51][52][53][54] (Fig. 3).…”
Section: Discussionmentioning
confidence: 77%
“…To analyze the importance of ATP hydrolysis during substrate secretion, the H662A mutant of HlyB, which is deficient in ATP hydrolysis, was used. This mutant is able to bind ATP, dimerization of the NBDs but does not catalyze ATP hydrolysis 27 29 . In combination with the concept of a stalled T1SS complex described above, the H662A mutant might help to clarify which step of substrate translocation is coupled to ATP hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Purification of HlyA and HlyAc was carried out as previously described 16 35 . HlyB was purified as described 29 . The concentration of the purified protein was determined spectrophotometrically (Nanodrop-1000, Thermo Scientific) using the calculated (web.expasy.org/protparam) extinction coefficient at 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…However, when comparing the data with known NBDs which has been described before in the presence and absence of the transmembrane segment it can be observed that v max might be changed, the k m values however remains very similar. For example the ATP hydrolysis kinetics have been described for the HlyB NBD as well as for the purified full length transporter in detergent solution 26,36,38,43,69 . Here the NBD showed a v max of 200 nmol min −1 mg −1 with a k m value of 0.31 where as the full length transporter displayed a lower v max of 8.1 nmol min −1 mg −1 with a k m value of 0.36.…”
Section: Discussionmentioning
confidence: 99%